Analysis of Effective Classroom Management Strategies to Create a Conducive Learning Environment for Elementary School Students through Document Studies - Afriadi, Bambang; Fitri, Fitri (LPPM Universitas Negeri Jakarta, 2023)
Effective classroom management is a crucial foundation in the success of learning in Primary School (SD), given the unique characteristics of students at this developmental age. This research aims to identify and analyze effective classroom management strategies that foster a conducive learning environment for elementary school students through a document study. The research method employed is qualitative, utilizing a literature review approach to analyze various sources, including scientific articles, textbooks, and research reports. The results of the analysis identified six main themes: (1) Preparation and Implementation of Clear Rules and Routines, (2) Development of Positive Teacher-Student Relationships, (3) Use of Active and Engaging Learning Strategies, (4) Implementation of Positive Reinforcement Techniques, (5) Implementation of Appropriate Proactive and Reactive Interventions, and (6) Creating a Supportive Classroom Physical Environment. These themes consistently appear in the literature as important factors in increasing student engagement, reducing disruptive behaviour, and creating a favourable classroom climate. This study concludes that effective classroom management in elementary school is multidimensional and requires the integration of various strategies that take into account the cognitive, social, and emotional aspects of students. The implications of this study underscore the importance of teacher professional development in adopting adaptive and evidence-based classroom management strategies to enhance the quality of learning at the primary education level.